1988
DOI: 10.1113/expphysiol.1988.sp003152
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Inflammatory Response During Involution of the Ovine Mammary Gland

Abstract: SUMMARYCessation of lactation, initiated by the removal of lambs from their mothers, induced an inflammatory response with elevated numbers of neutrophil leucocytes in mammary secretions being detected within 16 h. Leucocyte numbers were still elevated 7 d later. Infusion of whole milk into non-lactating glands caused no change in leucocyte numbers after 24 h. Involution secretions, however, had the capacity to induce an inflammatory response when infused into non-lactating glands. Daily infusion of endotoxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Although the early presence of neutrophils and the late presence of macrophages have been reported in the involution secretions of many species, including pigs, guinea pigs, sheep and cows [ 42 - 45 ], the same has not been reported for rats, humans or mice [ 30 ]. Our gene expression data strongly support a role for these cells during mouse mammary gland involution because the neutrophil-specific chemokine GRO1/CXCL1 was specifically upregulated fivefold on the first day of involution, and the neutrophilic-granulocyte marker LRG [ 46 ] was upregulated most strongly on day 2 after forced weaning (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the early presence of neutrophils and the late presence of macrophages have been reported in the involution secretions of many species, including pigs, guinea pigs, sheep and cows [ 42 - 45 ], the same has not been reported for rats, humans or mice [ 30 ]. Our gene expression data strongly support a role for these cells during mouse mammary gland involution because the neutrophil-specific chemokine GRO1/CXCL1 was specifically upregulated fivefold on the first day of involution, and the neutrophilic-granulocyte marker LRG [ 46 ] was upregulated most strongly on day 2 after forced weaning (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The opening of tight junctions in the case of once-daily milking could result from an inflammatory response due to the accumulation of milk in the cistern. It was observed that milk from distended udders of ewes exhibited more inflammatory activity (Colditz, 1988). Growth hormone has been reported to enhance neutrophil function and thus promote inflammation (Burvenich et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The methods used in this survey may provide a slight underestimate of the prevalence of infection because the threshold value for cell count on doubtful specimens was deliberately set at a high value (750,000 cells/ml). This value was selected on the basis of recent evidence from this laboratory indicating that lactating ewes which are separated from their lambs for 24 h often have quite high neutrophil counts in milk without evidence of infection (Colditz 1988).…”
Section: Discussionmentioning
confidence: 99%